Graphic abstract as a required element in manuscript submission and acceptance - Khan, Mohammad Rizwan; Xiong, Youling; Michniewicz, Martyna; Lesiów, Tomasz (Abstrakt graficzny jako element wymagany przy składaniu i akceptacji manuskryptu, 2021)
An increasing number of international journals in food science, technology, and nutrition require authors to include an illustrative and pictorial graphical abstract to concisely capture the essence of the study reported in the submitted manuscript. Numerous journals across different publishers implement this trending mandate. A typical graphical abstract consists of several individual graphs, pictures, or drawings, which are not necessarily derived from the experimental data collected, and the text should be kept very minimal. The images should clearly represent the work described in the paper. The graphical abstract is to be submitted as a separate file. Failure to include a graphical abstract at the time of manuscript submission will result in the automatic rejection of the paper, that is, the manuscript is deemed incomplete and thus will not be entered in the peer-review process
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2021, Nr 37, s. 113-122
Keywords: graphical abstracts; images; graphs; concise summary; abstrakt graficzny; obrazy; wykresy; zwięzłe streszczenie